БОҒЛИҚМАС ТАСОДИФИЙ СОНДАГИ ТАСОДИФИЙ МИҚДОРЛАР ЙИҒИНДИСИНИНГ МАКСИМУМИНИ БАҲОЛАШ ҲАҚИДА (Scientific journal of the Fergana State University, 2023)
In this paper we consider the estimate of the maximum of the sums of a random number of independent random variables